Dinamika Organisasi Kemasyarakatan di Kota Denpasar 1970-2014 - Nugraha, Anche; Suwitha, I Putu Gede; Gde Putra, Ida Bagus (Humanis; Volume 16. No. 1. Juli 2016, 2017)
Since the era of new order, the social organizations kept coming in Denpasar city. Every organizations with its characteristic trying to optimize owned a role in welfare improvements. After long established, the organization certainly dealing with reality social changes traversed throughout hostory. The development and changes of social environment, culture, economy, and politic, give impact which is functional to the development of social organization in Denpasar city. There are three main factors that causes many social organizations appeared in Denpasar city, consisting of the social, economy, and also politic. Contributions which have been shown to the public community organizations such as in the areas of social, cultural, and sport is shown by a variety of social service programs, blood donation, martial arts, and futsal.
Keywords: Organization, Social, Dynamics